Combination of Leukotoriene Receptor Antagonist With Antihistamine Has an Additive Suppressive Effect on the Up-regulation of H1-Receptor mRNA in the Nasal Mucosa of Toluene 2,4-Diisocyanate-Sensitized Rat - Wakana Kuroda; Yoshiaki Kitamura; Hiroyuki Mizuguchi; Yuko Miyamoto; Bukasa Kalubi; Hiroyuki Fukui; Noriaki Takeda (Elsevier, 2013)
Abstract.: An attempt was made to clarify the additive suppressive effects of pranlukast, a cysteinyl leukotriene-receptor (LTR) antagonist, in combination with chlorpheniramine, an antihistamine, on the up-regulation of histamine H1-receptor (H1R) mRNA in toluene 2,4-diisocyanate (TDI)-sensitized rats. Although pre-treatment with pranlukast partially, but significantly, suppressed TDI-induced up-regulation of H1R mRNA and nasal symptoms, pre-treatment with the combination of pranlukast and chlorpheniramine significantly suppressed them in a manner greater than either drug alone. These findings suggest that the additive therapeutic effect of the combination of LTR antagonist and antihistamine is due to their additive suppression of H1R up-regulation. Keywords:: antihistamine, cysteinyl leukotoriene receptor antagonist, histamine H1-receptor